Potential Role of Heritage Trail to Increase Property Value in Johor Bahru - Thasmeena A/P Ganesalingam (Research in Management of Technology and Business, 2023)
This research intends to study the potential of heritage trails and whether they might increase property value. Two (2) objectives have been outlined for this study: (i) to determine the correlation between the existence of heritage trail to the value of real estate sector, and (ii) to study the heritage trail effects. This research intends to study the potential of heritage trails and whether they might increase property value. A qualitative approach has been choosen whereby researcher collect and analyse qualitative data to support the information obtained through interview and Propert price data to draw the potential role of heritage trail to increase property value within the study area. Reseacher explore diverse perspectives and uncover relationships that exist between the intricate layers of multifaceted research questions. The researcher has interviewed officers from Malaysian Tourist Guide Council (MTGC), Think City, local authorities, property developers’ real estate negotiator and local communities in downtown Johor Bahru. Based on the results the researcher found various heritage trail benefits on the property value such as nearby property prices boom up, economically strong, attract a lot of investors to invest in the property and programmes conducted to sustain heritage trail in Johor Bahru. The findings of this study will be useful in closing the gap between government efforts toward public engagement practice. Moreover, the outcome of this study will provide the local communities, heritage managers, policymakers, and tourism industry players to understand the importance of heritage trails to promote area’s history as well as enhancing tourism image and local economic development.